Church–state relations and the decline of Catholic parties in Latin America. Issue 2 (3rd May 2016) - Mantilla, Luis Felipe
Abstract: The decline of Catholic parties across Latin America appears as an interesting exception to the global political resurgence of religion. Catholic parties, once important players in the region's politics, have become less distinctive or failed altogether. While many explanations focus on social secularization or the instability of regional politics, this article emphasizes the role of shifting relationship between the Catholic Church and Latin American states. Specifically, it argues that the emergence of flexible accoresearchers continue to catalog the myriad ways in whichmmodation, an arrangement whereby religious politics is managed by individual bishops, politicians and officials, has undermined the functionality and appeal of programmatic religious parties for elites and voters alike. As a result, Catholic religious politics remains vibrant, but is increasingly channeled outside the electoral arena.